Alarm system using programmable interface controller (PIC) / Mohamad Fauzi Omar - Omar, Mohamad Fauzi (1999)
This project invoives the design and development of an alarm system using PIC - (Programmable Interface Controller) microcontroller. The system consists of a controlling unit (CU) using PIC16F84 with EPROM (M27C256), a sensor unit (SU) and display unit (DU). Once detection is made the controller initiates software routines that will give a running display of the alarm triggered. The software for the system was developed on MPLAB package software for PIC and EPROM Data I/O programmer was used.